THE MECHANICAL BEHAVIOR OF A RANDOM THIN- WALLED AND POROUS METALLIC HOLLOW SPHERE - SONG JinLiang; ZHANG YiKang; SUN QuanSheng (Jixie qiangdu)
Cellular metal materials structure is a new type of porous metal material, it is made up by lots of metal hollow spheres（MHS）, and mechanical behavior research of the single metallic hollow sphere is the foundation of the whole material mechanical performance. The individual MHS with 2 mm to 3 mm outside diameter,10 μm to 40 μm thick walls with porosity were studied, and nano-indentation test, quasi-static uniaxial compression experiment and elastic compression test were performed on the metallic hollow spheres to get the Young’s modulus and hardness of the MHS and the material which was made up of the sphere, also single MHS compression deformation process and characteristics could be observed, finally simulated elastic stage of metallic hollow sphere by finite element software ABAQUS, analyzed the influence of the Young’s modulus of the whole MHS by porosity on thin wall, and result shows that with the porosity increasing, the elastic modulus of MHS will decrease, and present nonlinear distribution, it can be described the same format of a power law function as the relation of porosity with the porous thin wall.